1992
DOI: 10.1123/ijsn.2.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Thiamin, Iron, and Zinc Status in Elite Nordic Skiers during Different Training Periods

Abstract: This study evaluated how different training periods affect dietary intake and biochemical indices of thiamin, iron, and zinc status in elite Nordic skiers. Subjects.were 17 skiers and 39 controls, ages 18-38 yrs. Dietary data were collected by 7-day food records at 3-month intervals. Coefficient of variation (CV) was used to indicate magnitude of seasonal changes. Energy intake for the year (28 food record days) was 3,802 kcallday (CV 19.1%) in male skiers, 2,754 kcallday (CV 3.7%) in male controls, 2,812 kcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 35 publications
2
32
0
2
Order By: Relevance
“…Serum ascorbic acid concentrations were the same 49,54,75 or higher 76 in athletes than in controls. The pooled mean concentrations for serum or plasma ascorbic acid in the above studies were 59 and 56 mmol ⋅ L −1 for athletes (n = 533) and controls (n = 193), respectively.…”
Section: Vitamin Cmentioning
confidence: 67%
See 4 more Smart Citations
“…Serum ascorbic acid concentrations were the same 49,54,75 or higher 76 in athletes than in controls. The pooled mean concentrations for serum or plasma ascorbic acid in the above studies were 59 and 56 mmol ⋅ L −1 for athletes (n = 533) and controls (n = 193), respectively.…”
Section: Vitamin Cmentioning
confidence: 67%
“…The results in this cross-sectional study were adjusted for age, BMI, diet, smoking, serum cholesterol and serum triglycerides. Guilland et al 54 found comparable b-carotene levels in athletes and in controls.…”
Section: Indices Of Micronutrient Status In Physically Active Peoplementioning
confidence: 94%
See 3 more Smart Citations